THE EFFECT OF STORY PLAY THERAPY ON LANGUAGE DEVELOPMENT OF CHILDREN WITH MENTAL RETARDATION AT RELA SLB BHAKTI I GAMPING SLEMAN YOGYAKARTA - Tri Arini (UPT Penerbitan Universitas Jember, 2020)
Background: Retardation mental is child who has lack ability of adaptive behavior and intellectuals below average that appears during development process. The emergence of various developmental barriers in children with mental retardation is a phenomenon that needs to be further addressed so that the children with mental retardation can still live a good life and optimize the slightest their abilities, including increasing language skills. Purpose: To determine the effect of story play therapy on language development in children with mental retardation at SLB Rela Bhakti I Gamping Sleman Yogyakarta. Method: The type of research is Quasi-experimental with the design of